Lupus and vaccinations. Issue 5 (September 2018) - Mathian, Alexis; Pha, Micheline; Amoura, Zahir
Abstract : Purpose of review: To review the latest data in the field of vaccinations in systemic lupus erythematosus (SLE), focusing on pneumococcal, seasonal influenza, herpes zoster and human papillomavirus infections. Recent findings: Less than 40% of patients responded adequately to the 23-valent pneumococcal polysaccharide (PPS23) vaccine. A randomized controlled trial showed that sequential administration of the pneumococcal conjugate vaccine followed by the PPS23 vaccine was well tolerated but was not superior to the PPS23 vaccine alone in terms of immunogenicity. A real-life observation confirmed that annual influenza vaccination has an impact on morbidity and mortality in SLE. Three meta-analyses did not show any particular adverse effect of influenza vaccines in SLE. These vaccines are less immunogenic in SLE. A study confirmed that the quadrivalent human papillomavirus vaccine was well tolerated and highly immunogenic in SLE. Summary: New data confirm the safety and the lower immunogenicity of pneumococcal and influenza vaccine in SLE patients. Current efforts to improve immunization coverage in SLE should focus on spreading to patients and physicians information on the safety, efficacy and usefulness of vaccines in this population.